STEM CELL THERAPY ON ANIMAL MODEL (Rattus norvegicus) END GESTATIONAL TIME EXPOSED TO CARBON BLACK AS OBSERVED FROM CASPASE-3 EXPRESSION - Achmad, Agung Budianto; Madyawati, Sri Pantja; Widjiati, Widjiati (Journal of Vocational Health Studies, 2018)
Background: Air pollution in the form of Diesel Exhaust Particles emerging from motor vehicles are harmful to health that have adverse reproductive health impacts, especially during pregnancy. The use of stem cells in treating white mice (Rattus norvegicus) exposed to carbon black can reveal the potential for treatment of placental impairment during pregnancy. Purpose: to demonstrate the effectivity of Rat Bone Marrow Mesenchymal Stem Cell therapy on rats (Rattus norvegicus) exposed to carbon black as observed from caspase-3 expression. Method: This research uses a completely randomized design with factorial pattern. Forty-eight gravid female rats were divided into six treatment groups. Result: caspase-3 expression in each treatment showed no significant differences in the groups treated with RBMMSC in each gravid groups treatment (therapy GD 11 and GD 17) were exposed to carbon black and not treated with RBMMSC. The same are indicated by the normal trophoblast cells (cytotrophoblast and syncytiotrophoblast cells) in the RBMMSC treated group showed no significant difference with the group exposed to carbon black only. Conclusion: this research indicate that Rat Bone Marrow Mesenchymal Stem Cell therapy in Rattus norvegicus exposed to carbon black have not been able to reduce expression of caspase-3.